2011
DOI: 10.1016/j.bmcl.2011.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the leukotriene A4 hydrolase aminopeptidase augmentor 4-methoxydiphenylmethane in a pre-clinical model of pulmonary emphysema

Abstract: The leukotriene A4 hydrolase enzyme is a dual functioning enzyme with the following two catalytic activities: an epoxide hydrolase function that transforms the lipid metabolite leukotriene A4 to leukotriene B4 and an aminopeptidase function that hydrolyzes short peptides. To date, all drug discovery efforts have focused on the epoxide hydrolase activity of the enzyme, because of extensive biological characterization of the pro- inflammatory properties of its metabolite, leukotriene B4. Herein, we have designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Mice were exposed to either ambient air or cigarette smoke while being treated with either vehicle or a pharmaceutical agent (4MDM), which selectively augments the LTA 4 H aminopeptidase activity without affecting the LTA 4 H epoxy hydrolase activity. (25)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were exposed to either ambient air or cigarette smoke while being treated with either vehicle or a pharmaceutical agent (4MDM), which selectively augments the LTA 4 H aminopeptidase activity without affecting the LTA 4 H epoxy hydrolase activity. (25)…”
Section: Methodsmentioning
confidence: 99%
“…(3, 25, 27, 28) In brief, animals were deeply anesthetized with ketamine &xylazine mixture (60/5 mg per kg weight), the trachea was cannulated using p10 tubing, the sternum was opened, the diaphragm was cleared by opening the abdominal cavity, and animals were ventilated at a respiratory rate of 120 breaths per minute with PEEP 3 cm H 2 O per a pre-written macro program. This technique ensured that the live animals’ voluntary effort could not influence the physiologic values detected by the Flexivent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of 4-MDM to LTA 4 H enhances the degradation of PGP resulting in the decrease of neutrophil recruitment in the lung, and subsequently the reduction of inflammation with no effect on the epoxy hydrolase activity of LTA 4 H. Recent studies have demonstrated that oral administration of 4-MDM is effective against emphysema in mice induced by elastase and cigarette smoke. [1,8]. To establish the future clinical therapeutic dose and dosing regimen of 4-MDM, preclinical pharmacokinetic (PK) study is essential to characterize its PK in rodent and nonrodent animals.…”
Section: -Methoxydiphenylmethane (4-mdmmentioning
confidence: 99%
“…) is a selective augmenter of Leukotriene A 4 Hydrolase (LTA 4 H) aminopeptidase enzyme activity and a new anti-inflammatory compound for chronic obstructive pulmonary disease (COPD) [1]. LTA 4 H Abbreviations: 4-MDM, 4-methoxydiphenylmethane; ACN, acetonitrile; APPI, atmospheric pressure photoionization; BCS, biopharmaceutical classification system; CAD, collision activated dissociation; CE, collision energy; COPD, chronic obstructive pulmonary disease; CEP, collision cell entrance potential; CXP, collision cell exit potential; DP, decluttering potential; EP, entrance potential; IE, ionization energy; LLOQ, lower limit of quantification; LTA4H, leukotriene A4 hydrolase; LTB4, leukotriene B4; PA, proton affinity; PI, photoionization; PGP, proline-glycineproline; PK, pharmacokinetics; RCF, relative centrifugal force; SD, Sprague Dawley.…”
Section: -Methoxydiphenylmethane (4-mdmmentioning
confidence: 99%